Ideal Time for Preoperative Use of Indocyanine Green Dye in Laparoscopic Cholecystectomy An Observational Study at A Tertiary Care Hospital - Togale, Manoj; Gogate, Abhishek; Gogate, Abhijit; Sharma, Ayushman (Journal of Neonatal Surgery, 2025)
N\A